Bioconversion of chicken feathers by Bacillus aerius NSMk2: A potential approach in poultry waste management. (September 2018) - Bhari, Ranjeeta; Kaur, Manpreet; Singh, Ram Sarup; Pandey, Ashok; Larroche, Christian
Abstract: About 73 bacterial strains were isolated from poultry dump sites in Punjab and an isolate showing high keratinolytic activity was identified as Bacillus aerius NSMk2. Strain showed prompt hydrolysis of white chicken feathers on minimal salt medium (MSM) after 5 days of cultivation. Melanized chicken, pigeon and duck feathers could also be degraded by bacteria with high activity to duck and pigeon feathers. MSM supplemented with fructose and beef extract supported higher feather keratinase production and improved degradation of white chicken feathers. Feather concentration 1.375%, pH 7.5 and temperature 35 °C showed maximum feather keratinase activity (127.63 U/ml) after 2 days which was 7-fold higher than activity on minimal salt medium. Time for complete degradation of white chicken feathers was reduced to 3 days on optimized medium. The results of present investigation showing potential keratinolytic ability of Bacillus aerius NSMk2 could provide an environmental friendly approach for bioconversion of poultry waste. Highlights: High keratinolytic potential of Bacillus aerius NSMk2. Efficient degradation of different bird feathers (chicken, pigeon and duck). Time for complete of white chicken feathers reduced to 3 days by optimization.